2022
DOI: 10.3390/plants11243462
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Induced Intensification of Deoxyshikonin Production in Rindera graeca Hairy Root Cultures with Ester-Based Scaffolds

Abstract: In vitro plant cell and tissue culture systems allow for controlling a wide range of culture environmental factors selectively influencing biomass growth and the yield of secondary metabolites. Among the most efficient methods, complex supplementation of the culture medium with elicitors, precursors, and other functional substances may significantly enhance valuable metabolite productivity through a stress induction mechanism. In the search for novel techniques in plant experimental biotechnology, the goal of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Details of band assignments are given in Table . Similar results for neat PLA have also been found by other researchers. However, in Figure b, for the low-, medium-, and high-crystalline PLAs that were irradiated at 250 kGy with 80 °C (0-T80D250, 5-T80D250, and 20-T80D250), the vibrations at 2922 and 2852 cm –1 become much stronger than those of their neat counterparts. Concerning the thermo-oxidative degradation, which will not lead to a −CH 2 – group vibration enhancement in the wavenumber range of 3040 to 2800 cm –1 , the increase of −CH 2 – group vibration at 2922 and 2852 cm –1 is unlikely to be attributed to the chain scission caused by the small amount of residual oxygen (we irradiated under nitrogen) or elevated temperature during irradiation .…”
Section: Resultsmentioning
confidence: 95%
“…Details of band assignments are given in Table . Similar results for neat PLA have also been found by other researchers. However, in Figure b, for the low-, medium-, and high-crystalline PLAs that were irradiated at 250 kGy with 80 °C (0-T80D250, 5-T80D250, and 20-T80D250), the vibrations at 2922 and 2852 cm –1 become much stronger than those of their neat counterparts. Concerning the thermo-oxidative degradation, which will not lead to a −CH 2 – group vibration enhancement in the wavenumber range of 3040 to 2800 cm –1 , the increase of −CH 2 – group vibration at 2922 and 2852 cm –1 is unlikely to be attributed to the chain scission caused by the small amount of residual oxygen (we irradiated under nitrogen) or elevated temperature during irradiation .…”
Section: Resultsmentioning
confidence: 95%
“…One of the practical bioengineering techniques widely recognized as a high-potential solution for the intensification of secondary plant metabolite production is in situ extraction [16][17][18][19]. Moreover, such a technique also provides a favorable microenvironment for the de novo production of secondary metabolites, which do not occur in the natural environment [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…It has been documented that the application of biopolymers in plant or plant organ cultures could improve plant growth and the accumulation of medicinal components [19][20][21][22][23][24][25][26][27][28][29]. Chang et al [24] showed that biopolymer polylactic acid (PLA) stimulated the growth of soybeans.…”
Section: Introductionmentioning
confidence: 99%
“…Patil et al [27] reported that different biopolymers, agar, cellulose, alginate, psyllium gaur gum, and bacterial exopolysaccharide (EPS), all improved the seedling growth of Gossypium herbaceum L. Zagzog et al [29] also demonstrated that chitosan improved the vegetative growth of mangos. Wierzchowski et al [23] found that PLA could promote biomass proliferation of Rindera graeca hairy root. Additionally, previous studies have also proved that biopolymers could also improve the accumulation of medicinal components in the culture of plant hairy root [19][20][21][22][23]25,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation